Factors of repatriates’ turnover: literature review - Martins, Dora (2015)
One of the important challenges for multinational organisations is to increase the ability to retain their repatriates. The literature review shows high turnover rates amongst repatriates in the first two years following return from the international assignment. This paper discusses organisation’s (in)ability to retain its repatriates. A diversity of predictable factors of repatriates’ turnover is identified, including factors related to the job, the organisation, qualification, career development, personality, social context and the market. The paper analysis organisational support practices designed to increase the power of retention and decrease the turnover. We concluded that research about retention versus turnover of repatriates is scarce, mainly regarding the role a formal repatriation and retention programme in facilitating the retention of these employees with acquired international knowledge and skills, that is, the role that organisational factors play in voluntary turnover decisions. Further research is suggested at the end of the article.